Optimasi Pendapatan Pembuatan Spanduk dan Baliho Menggunakan Metode Simpleks (Studi Kasus: Usaha Percetakan Shiau Printing) - Matheus Supriyanto Rumetna; Otniel Otniel; Friendly Litaay; Carlie Sibarani; Ruben Tahrin; Tirsa Ninia Lina; Ratna Rosmauli Pakpahan (STMIK Budi Darma, 2020)
Shiau Printing is one of the businesses engaged in printing. This business often experiences production optimization problems, namely in terms of determining the maximum profit from the two types of products produced, namely banners and billboards. Constraints faced in the form of limited production resources, such as flexi materials. This problem can be solved by implementing linear programming using the simplex method and then testing it using the POM-QM application for Windows. Based on the results of calculations that have been made, a decision was drawn that the Shiau Printing could obtain a maximum income of IDR 15,000,000 -, / month.